Occurrence of methicillin resistant Staphylococcus aureus in chickens and farm personnel in Sokoto, North-western Nigeria - Kwoji, Iliya Dauda; Tambuwal, Farouk Muhammad; Abubakar, Mikaeel Bala; Yakubu, Yusuf; Bitrus, Asinamai Athliamai; Jauro, Solomon (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The study was conducted to determine the presence of methicillin resistant Staphylococcus aureus (MRSA) in chickens and farm personnel in Sokoto, North-western Nigeria. Materials and method: A total of 160 samples (136 from chickens and 14 from personnel) were collected and screened for the presence of MRSA using cultural characteristics, biochemical tests and latex slide agglutination test for the presence of Penicillin binding protein 2? (PBP2?). Results: MRSA were detected in 8.82% (n=12/136) of chickens, while 14.29% (n=2/14) in farm personnel. All the isolates were positive for PBP2?. Conclusion: This study established for the first time the occurrence of MRSA in both chickens and farm personnel from poultry farms in Sokoto, Nigeria. Thus, the study provided baseline information for further studies on the epidemiology of MRSA. http://doi.org/10.5455/javar.2017.d220